ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF CYNOMETRA IRIPA KOSTEL. - Mrunalini N.Desai; N.S. Chavan. (International Journal of Pharma and Bio Sciences, 2010)
Antimicrobial activity of aerial parts of Cynometra iripa Kostel was evaluated against Bacillus cereus, Staphylococcus aureus, Pseudomonas aerunginosa, and Salmonella typhimurium. Ethanolic and methanolic extracts of plant parts were screened for antibacterial activity. Methanolic extracts of leaf, stem, young seed, mature seed and seed coat showed a high antibacterial activity against Pseudomonas aerunginosa as compared to ethanolic extracts products. Preliminary tests for different chemical groups showed the presence of polyphenols, tannins, flavonoids and saponins.